Factors Affecting Passenger Satisfaction in Using Self Check-in at Soekarno-Hatta International Airport - Angel Lawrentina Christiana Sihombing; Sitti Zahara Saiful; Edi Abdurachman; Primadi Candra Susanto (Siber Nusantara Research & Yayasan Sinergi Inovasi Bersama (SIBER), 2026)
This study was conducted to determine whether customer satisfaction is influenced by the usefulness and ease of use of the technology system on the self check-in machine so that it can be optimized and reduce check-in queues at the Soekarno-Hatta airport check-in counter. This research was conducted at Soekarno-Hatta airport. The method used in this research is quantitative with structural equation model analysis, the data collected using questionnaire techniques distributed to passengers at Soekarno-Hatta airport who use self check-in machines with a sample size of 100 respondents. The results of the calculation show that there is an effect of the easy of use of the self-check-in machine on passenger satisfaction and the usefulness of the self-check-in machine has proven significant with a P value below 0.000, indicating this study confirms that the easy of use of the self-check-in machine affects passenger satisfaction and the usefulness of the self-check-in machine affects passengers satisfaction. With this research, it is hoped that it can help Soekarno-Hatta Airport to develop a self check-in machine system that is safe and easy to use.